The Relationship Between Knowledge And Attitude Of Adolescents About Genital Hygiene During Menstruation: HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA TENTANG KEBERSIHAN ALAT KELAMIN PADA SAAT MENSTRUASI - Dwi Y, Annisa; Gita, Irma; Risdianti, Helza; Devi; Rahma; M, Tri; Reny; Yanti, Tisna; Suryaman, Ratih; Hari, Fitria (Jurnal Penelitian Keperawatan Kontemporer, 2025)
Background: Puberty in women usually occurs between the ages of 13 to 16 years. This period is characterized by female reproductive organs that show drastic changes, because there is already growth of ovarian primordial follicles that secrete hormonal estrogen, which is the most important hormone in women. The release of this hormone fosters secondary sex signs, one of which is the occurrence of blood discharge called menstruation. Objective: To determine the relationship between knowledge and attitude of adolescents about genital hygiene during menstruation. Methods: This study is a correlational analytic with a cross sectional approach. The population in this study were 158 people, the number of samples in this study amounted to 44 respondents with Random Sampling technique. The results of the study were tested with the Kendall tau statistical test with a significance of α = <0.05 with the SPSS 25 program. The research instrument used a knowledge questionnaire and an attitude questionnaire. This research was conducted at SMK Teknomedika Plus Bogor Regency. Results: The results of the Kendall tau test with an error rate (α) = 0.05, obtained a p value = 0.000. This means that Ha is accepted and H0 is rejected. Conclusion: There is a significant relationship between knowledge and attitude of adolescent girls towards genital hygiene during menstruation at SMK Teknomedika Plus Bogor Regency.